Prevention of thromboembolic complications in patients with atrial fibrillation and obesity - Izabela Kolasa; Beata Średniawa (Śląski Uniwersytet Medyczny w Katowicach, 2023)
Atrial fibrillation (AF) is an arrhythmia that occurs in 1-2% of the population. Chronic oral anticoagulation is recommended in the group of patients with AF to prevent thromboembolic complications. Obesity is a factor contributing to the development and progression of AF, and the use of oral anticoagulants in patients with excess body fat may be difficult. Vitamin K antagonist (VKA) and non-vitamin K antagonist oral anticoagulants (NOAC) are commonly used. For VKA in obese patients, a longer time and a higher dose of drugs should be expected to achieve the target international normalized ratio (INR) values. It is not known whether the therapeutic range of INR should change with the body mass index (BMI) or body weight. NOACs include factor Xa inhibitors and direct thrombin inhibitors. The use of NOAC in obese patients has been proven to be effective and safe. In the group of patients with AF and morbid obesity or with a body weight > 120 kg, the use of VKA or determination of the plasma concentration should be considered in the prevention of thromboembolic complications due to the limited amount of data.